Optimal Linear Controller Design for Periodic Inputs - Pipeleers, Goele. (Lecture Notes in Control and Information Sciences,, 2009)
Optimal Linear Controller Design for Periodic Inputs proposes a general design methodology for linear controllers facing periodic inputs which applies to all feedforward control, estimated disturbance feedback control, repetitive control and feedback control. The design methodology proposed is able to reproduce and outperform the major current design approaches, where this superior performance stems from the following properties: uncertainty on the input period is explicitly accounted for, periodic performance being traded-off against conflicting design objectives and controller design being translated into a convex optimization problem, guaranteeing the efficient computation of its global optimum. The potential of the design methodology is illustrated by both numerical and experimental results.